Variation between glaucous and non-glaucous near-isogenic lines of rye (Secale cereale L.) under drought stress - Laskoś, Kamila; Myśków, Beata; Dziurka, Michał; Warchoł, Marzena; Dziurka, Kinga; Juzoń, Katarzyna; Czyczyło-Mysza, Ilona M. (Scientific reports, 2022)
Glaucous (811, L35, and RXL10) and non-glaucous (811bw, L35bw, and RXL10bw) near-isogenic lines (NILs) of rye ( Secale cereale L.) forming three pairs of inbred lines were the subject of the research. The research aimed to study the relationship between wax cover attributes and the physio-biochemical drought reactions and yield of rye NILs and to uncover the differences in drought resistance levels of these lines. The greatest differences between glaucous and non-glaucous NILs were observed in the RXL10/RXL10bw pair. Of particular note were the stable grain number and the thousand grain weight of the non-glaucous line RXL10bw under drought and the accompanying reactions, such as an approximately 60% increase in MDA and a two-fold increase in wax amount, both of which were significantly higher than in the glaucous line RXL10 and in other NILs. The surprisingly high level of MDA in the RXL10bw line requires further analysis. Moreover, additional wax crystal aggregates were found under drought conditions on the abaxial leaf surface of the glaucous lines 811 and RXL10. The use of rye NILs indicated that line-specific drought resistance could be associated with wax biosynthetic pathways involved in physiological and biochemical responses important for increased drought resistance.